Effect of calcination temperature on preparation and electrochemical characterization of Ti/Sn-Sb-RuOx electrode for zinc electrowinning. (30th August 2019) - Liu, Jianhua; Li, Runping; Wang, Teng; Chen, Buming
Abstract: The variations in the electrochemical characterization of Ti/Sn-Sb-RuOx electrodes prepared using thermal decomposition technique with various calcination temperatures are discussed in this work. The microscale morphology and physical composition of the fabricated electrodes are characterized by scanning electron microscopy and x-ray diffraction. Cyclic voltammetry tests are also performed to evaluate the electrochemical performance. The experimental data showed that the electrochemical characterization of prepared Ti/Sn-Sb-RuOx electrodes was inversely related to the calcination temperature. The surface morphology was a block crack structure. As the calcination temperature increased, the crack gradually broadened and deepened. The diffraction peak of RuO2 rised to the maximum at 500 °C. The temperature continued to rise, the diffraction peak of RuO2 decreased. The electrode prepared at 500 °C had the largest voltammetric capacity and a larger electrochemical active area. The service life of the electrodes prepared at 500 °C was longer than that of the electrode prepared at other temperatures.